2012
DOI: 10.1038/nature11593
|View full text |Cite
|
Sign up to set email alerts
|

Rapid coupling between ice volume and polar temperature over the past 150,000 years

Abstract: Current global warming necessitates a detailed understanding of the relationships between climate and global ice volume. Highly resolved and continuous sea-level records are essential for quantifying ice-volume changes. However, an unbiased study of the timing of past ice-volume changes, relative to polar climate change, has so far been impossible because available sea-level records either were dated by using orbital tuning or ice-core timescales, or were discontinuous in time. Here we present an independent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
722
1
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 545 publications
(760 citation statements)
references
References 32 publications
32
722
1
5
Order By: Relevance
“…10). At the same time the Dead Sea had elevated water levels (Torfstein et al, 2015), in agreement with the humid climate inferred for the eastern Mediterranean and increased Nile floods, leading to the formation of sapropel S5 (Grant et al, 2012). For the period of 128 to 123 ka Milner et al (2012) have suggested pronounced seasonality with increased summer aridity and winter precipitation on the basis of acicular aragonite formation (indicating enhanced evaporation) in an otherwise aquatic phase of the Tenaghi Philippon peatland (NE Greece).…”
Section: Fig 11supporting
confidence: 52%
“…10). At the same time the Dead Sea had elevated water levels (Torfstein et al, 2015), in agreement with the humid climate inferred for the eastern Mediterranean and increased Nile floods, leading to the formation of sapropel S5 (Grant et al, 2012). For the period of 128 to 123 ka Milner et al (2012) have suggested pronounced seasonality with increased summer aridity and winter precipitation on the basis of acicular aragonite formation (indicating enhanced evaporation) in an otherwise aquatic phase of the Tenaghi Philippon peatland (NE Greece).…”
Section: Fig 11supporting
confidence: 52%
“…This is insufficient to explain the large LGM-to-PGM environmental contrast, so we conclude that sea level dropped much more during the LGM than in the PGM. (Grant et al, 2012); MS21 (32 20.7 0 N, 31 39.0 0 E, 1022 m water depth) (Hennekam, 2015); M40-67 (34.814167 N, 27.296000 E, water depth 2157 m), and M40-71 (34.811160 N, 23.194160 E, water depth 2788 m) (Weldeab et al, Fig. 1.…”
Section: Denton and Hughes 2002mentioning
confidence: 99%
“…Near-continuous records can be evaluated probabilistically, accounting for both age uncertainties and sea-level uncertainties. These assessments identify probability maxima and their 95% probability bounds (Grant et al, 2012Rohling et al, 2014), which we use here. The two basins are independent; they are not connected, and link with separate oceans with different climate and ocean circulation dynamics (Schott et al, 2009;Buckley and Marshall, 2016).…”
Section: Red Sea and Mediterranean Recordsmentioning
confidence: 99%
See 2 more Smart Citations